Reframing Authority—The Role of Media and Materiality. Issue 3 (16th November 2017) - Feldt, Laura
Abstract : This is the introduction for the special issue, which discusses our common questions and perspectives. It offers an introductory discussion of the key concepts - authority, materiality and media - and it presents the four articles of the special issue.